Long-Term Hindrance Effects of Algal Biomatter on the Hydration Reactions of Ordinary Portland Cement - Lin, Meng-Yen; Grandgeorge, Paul; Jimenez, Andrew M.; Nguyen, Bichlien; Roumeli, Eleftheria (ACS Sustainable Chemistry & Engineering, 2023)
The incorporation of carbon-fixing materials such as photosynthetic algae in concrete formulations offers a promising strategy toward mitigating the concerningly high carbon footprint of cement. Prior literature suggests that the introduction of up to 0.5 wt % chlorella biological matter (biomatter) in ordinary Portland cement induces a retardation of the composite cement’s strength evolution while enabling a long-term compressive strength comparable to pure cement at a lower carbon footprint. In this work, we provide insights into the fundamental mechanisms governing this retardation effect and reveal a concentration threshold above which the presence of biomatter completely hinders the hydration reactions. We incorporate Chlorella or Spirulina, two algal species with different morphology and composition, in ordinary Portland cement at concentrations ranging between 0.5 and 15 wt % and study the evolution of mechanical properties of the resulting biocomposites over a period of 91 days. The compressive strength in both sets of biocomposites exhibits a concentration-dependent long-term drastic reduction, which plateaus at 5 wt % biomatter content. At and above 5 wt %, all biocomposites show a strength reduction of more than 80% after 91 days of curing compared to pure cement, indicating a permanent hindrance effect on hardening. Characterization of the hydration kinetics and the cured materials shows that both algal biomatters hinder the hydration reactions of calcium silicates, preventing the formation of calcium hydroxide and calcium silicate hydrate, while the secondary reactions of tricalcium aluminate that form ettringite are not affected. We propose that the alkaline conditions during cement hydration lead to the formation of charged glucose-based carbohydrates, which subsequently create a hydrogen bonding network that ultimately encapsulates calcium silicates. This encapsulation prevents the formation of primary hydrate products and thus blocks the hardening of cement. Furthermore, we observe new hydration products with composition and micromorphology deviating from the expected hardened cement compounds. Our analysis provides fundamental insights into the mechanisms that govern the introduction of two carbon-negative algal species as fillers in cement, which are crucial for enabling strategies to overcome the detrimental effects that those fillers have on the mechanical properties of cement.